A multi‐faceted intervention to reduce alcohol misuse and harm amongst sports people in Ireland: A controlled trial. (7th August 2017) - O'Farrell, Anne; Kingsland, Melanie; Kenny, Susan; Eldin, Nazih; Wiggers, John; Wolfenden, Luke; Allwright, Shane
Abstract: Introduction and Aims: Alcohol misuse and harm are more prevalent amongst sports people than non‐sports people. Few studies have trialled interventions to address alcohol misuse for this group. The study aimed to test the effectiveness of an intervention to reduce alcohol misuse and related harms amongst amateur sports people in Ireland. Design and Methods: A controlled trial was conducted in two counties in Ireland. A random selection of sports clubs in one county received a 4 month multi‐faceted intervention. All sports clubs in a non‐adjacent county acted as control sites. Consumption of more than 21 units of alcohol per week and six or more standard drinks on a single occasion at least once per week was the primary study outcome. Alcohol Use Disorders Identification Test scores and number of alcohol‐related harms were also reported. Outcomes were assessed for cross‐sectional samples of players at pre‐intervention and post‐intervention and paired samples of players who completed surveys at both times. Generalised linear mixed model analysis was used. Results: There was no evidence of effect for the primary outcomes or Alcohol Use Disorders Identification Test scores. There was a statistically significant difference in the median number of alcohol‐related harms reported by intervention group players compared with control group players at post‐intervention for the paired samples [intervention: 0; control: 3; incident rate ratio 0.56 (0.37, 0.84); P = 0.005]. Discussion and Conclusions: Intervention in community sports clubs may be effective in reducing the number of alcohol‐related harms. Low levels of intervention participation and inadequate intervention dose are possible reasons for lack of a broader intervention effect. [O'Farrell A, Kingsland M, Kenny S, Eldin N, Wiggers J, Wolfenden L, Allwright S. A multi‐faceted intervention to reduce alcohol misuse and harm amongst sports people in Ireland: A controlled trial. Drug Alcohol Rev 2018;37:14–22]